2005
DOI: 10.2143/ac.60.3.2005010
|View full text |Cite
|
Sign up to set email alerts
|

Miderm follow-up after off-pump versus on-pump coronary artery bypass grafting

Abstract: OPCAB surgery is a safe and reproducible technique, yielding short-and midterm outcomes comparable to conventional CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Also Kaplan-Meier estimation analysis showed similar results between groups (Log-Rank p = 0.064). In our study the number of grafts was similar to the results by Lycops et al [19]. Interestingly, in terms of 5-year survival Lycops et al revealed 78% in OPCAB group and 68% in on-pump group, whereas we found a 7-year follow-up survival rate of 81% in OPCAB surgery and 89% in on-pump group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also Kaplan-Meier estimation analysis showed similar results between groups (Log-Rank p = 0.064). In our study the number of grafts was similar to the results by Lycops et al [19]. Interestingly, in terms of 5-year survival Lycops et al revealed 78% in OPCAB group and 68% in on-pump group, whereas we found a 7-year follow-up survival rate of 81% in OPCAB surgery and 89% in on-pump group.…”
Section: Discussionsupporting
confidence: 91%
“…OPCAB may be a better alternative because of decreased blood loss, and shorter hospital stay [1, 18]. Previously published studies comparing the effect of off-pump versus on-pump CABG on clinical end-points with respect to renal impairment have yielded conflicting results [9, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance of extracorporeal circulation (ECC) emerged as a valuable alternative for conventional coronary surgery, but tends to have significantly lower frequencies of complete revascularization, which could lead to repeated procedures and increased mortality, irrespective of the technical difficulties. 3-5 Due to the fact that off-pump techniques apply only to coronary surgery (OPCAB), ECC is still necessary for valve surgery procedures where the heart chambers need to be opened for surgical repair. Minimally invasive extracorporeal circulation (MiECC) has been developed in an attempt to integrate all advances in cardiopulmonary bypass technology in one closed circuit, classified in four different types according to Anastasiadis et al 6…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other studies comparing data of conventional and beating-heart cardiac operations found that cardioplegic arrest did not increase the incidence of postoperative AF. 9 -13 Lycops et al, 14 comparing off-pump and on-pump groups with similar preoperative characteristics, found that the incidence of AF did not differ between groups.…”
Section: Discussionmentioning
confidence: 99%